PH-responsive prodrug nanoparticles based on xylan-curcumin conjugate for the efficient delivery of curcumin in cancer therapy. (15th May 2018) - Sauraj,; Kumar, S. Uday; Kumar, Vinay; Priyadarshi, Ruchir; Gopinath, P.; Negi, Yuvraj Singh
Highlights: pH-responsive xyl-cur prodrug NPs were prepared by dialysis membrane method. Xyl-cur prodrug NPs showed pH-responsive drug released behavior. Xyl-cur prodrug NPs are biocompatible and safe for intravenous administration. Xyl-cur prodrug NPs demonstrated higher cytotoxic activity than free curcumin. Abstract: In the present study, novel pH-responsive prodrug nanoparticles based on xylan-curcumin (xyl-cur) conjugate were developed to enhance the therapeutic efficacy of curcumin in cancer therapy. The synthesis of xyl-cur conjugate (prodrug) was confirmed by FT-IR, 1 H NMR, UV–vis and fluorescence spectroscopy. The xyl-cur prodrug was subsequently self-assembled in to nanoparticles (xyl-cur prodrug NPs) in an aqueous medium with the average particle size 253 nm and the zeta potential of −18.76 mV. The xyl-cur prodrug NPs were highly pH-sensitive in nature and most of the drug was released at lower pH. The interaction of the xyl-cur prodrug NPs with blood components was tested by hemolysis study. The cytotoxic activity of the xyl-cur prodrug NPs against human colon cancer cells (HT-29, HCT-15) demonstrated that the prodrug NPs exhibits greater cytotoxic effect than curcumin. Therefore, these results reveal that xyl-cur prodrug NPs could be a promising candidate for improving the intracellular delivery of curcumin in cancer therapy.